2012
DOI: 10.1042/bj20111929
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cellular S1P levels with a novel, potent and specific inhibitor of sphingosine kinase-1

Abstract: SphK (sphingosine kinase) is the major source of the bioactive lipid and GPCR (G-protein-coupled receptor) agonist S1P (sphingosine 1-phosphate). S1P promotes cell growth, survival and migration, and is a key regulator of lymphocyte trafficking. Inhibition of S1P signalling has been proposed as a strategy for treatment of inflammatory diseases and cancer. In the present paper we describe the discovery and characterization of PF-543, a novel cell-permeant inhibitor of SphK1. PF-543 inhibits SphK1 with a K(i) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
282
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(300 citation statements)
references
References 37 publications
15
282
3
Order By: Relevance
“…4B , inset) revealed an IC 50 value of 16 nM. A previous study using 1 µM FITC-Sph as a substrate reported an IC 50 of 3.6 nM ( 19 ). SphK1 inhibition kinetics with DMS revealed an IC 50 of 15.2 µM ( Fig.…”
Section: Fluorescence Assays In 384-well Plate Format For Sphk Inhibimentioning
confidence: 90%
See 2 more Smart Citations
“…4B , inset) revealed an IC 50 value of 16 nM. A previous study using 1 µM FITC-Sph as a substrate reported an IC 50 of 3.6 nM ( 19 ). SphK1 inhibition kinetics with DMS revealed an IC 50 of 15.2 µM ( Fig.…”
Section: Fluorescence Assays In 384-well Plate Format For Sphk Inhibimentioning
confidence: 90%
“…However, the signal is too low to accurately measure basal SphK activity. Importantly, overexpressed SphK1 activity was strongly inhibited by PF-543 ( 19 ), showing specifi city to a SphK1 catalyzed reaction ( Fig. 2H ).…”
Section: Fluorescence Sphk Assays In 384-well Plate Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the impact of LPS stimulation on sphingolipid content of primary macrophages cultured for 16 h in the presence of 500 M palmitate, we used LC-MS/MS to examine metabolites in this pathway (24). As seen in Table 1 and Fig.…”
Section: Lps and Palmitate Lead To Synergistic C16 Ceramide Productiomentioning
confidence: 99%
“…Although SphK1 is elevated in lung cancer patients suggesting a potentially important role for this enzyme in lung tumor cell proliferation and survival [43,53], results with novel, highly potent, and selective inhibitors to SphK1 in tumor cells did not affect their growth in vitro or in vivo, suggesting that tumor SphK1 may not be an efficacious therapeutic target for cancer [54,55]. Hence, inhibitors of SphK2 are developed and tested for inducing lung cancer cell death, among which ABC294640 is a first-in-class drug [56].…”
Section: 1mentioning
confidence: 99%